40th Winter School on Vibroacoustical Hazards Suppressions Szczyrk, Poland, February 27 –March 2, 2012 - BUKOWSKI, Roman (Archives of Acoustics, 2012)
Traditionally you are invited to acquaint yourselves with some abstracts of lectures submitted to the 40th Winter School on Vibroacoustical Hazards Suppres- sions. This national School is traditionally held at the turn of February and March and is organized in differ- ent places of Silesian Beskidy Mountains. This year it is again held in Szczyrk. This year we celebrate the jubilee edition of the School. Because of this anniversary the conference apart from standard organizers, i.e. Upper Silesian Di- vision of the Polish Acoustical Society and Institute of Physics – Science-Didactic Center at the Silesian University of Technology, has also a co-organizer – the Committee on Acoustics of the Polish Academy of Sci- ences. Moreover there are two splendid honorary pa- trons – Prof. Zbigniew Engel, president of the Com- mittee on Acoustics of the Polish Academy of Sciences, and Prof. Andrzej Bluszcz, director of the Institute of Physics – Science-Didactic Center at the Silesian Uni- versity of Technology. The conference is a forum for all environmen- tal vibroacoustic fields. Particularly it concerns traf- fic noise, industry noise, vibroacoustics of machines, room acoustics, noise protection and similar problems. Works which are presented during the School are the- oretical, experimental, measuring, technical, applied and normative. The program of the 40th edition of the School is very rich – there are some occasional lec- tures to celebrate our anniversary and many plenary lectures which recapitulate different achievements in Polish environmental acoustics. It should be mentioned that this year Polish acousticians celebrate the cen- tennial birthday of a famous Polish scientist, Ignacy Malecki. The School lectures and other conference materials will be published in the “Materials of the XL Winter School on Vibroacoustical Hazards Suppressions” (in Polish) edited by dr. Roman Bukowski. This publica- tion will be intended for participants of the School and for many libraries in Poland.